Ad PENETAPAN KANON KITAB SUCI PERJANJIAN LAMA DALAM GEREJA KATOLIK : 1. Pengertian kanon - Ambrianus Arsiwin; Usman, Yosef (Sphatika: Jurnal Teologi, 2025)
The establishment of the Old Testament Canon in the Catholic Church is a long and complex process that aims to determine which books are legitimately recognized as part of the Bible. The establishment of the Canon of Old Testament Scripture in the Catholic Church is so complex that there are various types of implementation of the canon of Old Testament Scripture and commentaries of biblical scholars, as well as the explanation of Old Testament Scripture to other religious communities. The division of the canon of Old Testament Scripture that is used today has criteria, it did not just appear out of nowhere and this must be considered carefully. Then there is the difference between the Jewish, Catholic, Orthodox and Protestant canons, as well as the division of the Old Testament Scriptures from the Pentateuch, the Historical Books, the Wisdom Books and the Apocryphal books. It is evident that the official listing of a work takes into account its author, content, and usefulness. In the context of the Old Testament Scriptures, canon means the official list of books recognized by the Catholic/Protestant/Orthodox Church/ or the Jewish religion after a long process of selection and determination. The existence of this official list of books means that it is no longer possible to reduce or add to it (cf. Deut. 4:2).